Mastering organic chemistry via organix battleship games: a statistical study - Mohd Ali, Noor Saadiah; Mat Russ, Nazirah; Mohd Hafidz, Ismail Fitri; Ramlan, Nor Siti Hawa; Parmin, Siti Ruziani; Mustafa, Nooraidah; Nik Mohamed, Nik Rahmah; Jamauddin, Rosmaya; Md Nor, Nurur Raudzah (ASIAN SCHOLARS NETWORK, 2025)
Organic chemistry is a branch of chemistry that focuses on the study of the structure, properties, reactions, and synthesis of carbon-containing compounds. Some students find organic chemistry is challenging due to its complexity and the need to understand intricate molecular structures and memorizing the reactions. This innovation developed a learning tool that integrate organic chemistry content into 2D mobile game namely OrganiX Battleship. This game aimed to keep the students engaged and motivate them, to study anywhere and anytime by using mobile platform. The game was incorporated with exercises with different difficulty level tailored with the learning module. This OrganiX Battleship is used in Chemistry 2 course for Sciences students in Centre for Foundation Studies, IIUM. A combination of descriptive statistics, specifically mean values, and inferential statistics using Partial Least Squares Structural Equation Modelling (PLS-SEM) was adopted to gain a comprehensive understanding of the impact and dynamics of the gamification approach. Results revealed that OrganiX Battleship increase their understanding, motivation, and engagement in learning organic chemistry. Gamification alleviates the monotony of studying chemistry, making it more engaging for students and enhancing their ability to memorize organic compounds and reactions. This OrganiX Battleship mobile game has potential for commercialization that can create a compelling and engaging mobile gaming experience.